WAYANG ORANG SEBAGAI PERTUNJUKAN TEATER TRADISIONAL DALAM TINJAUAN SEMIOTIKA : (Sebuah kajian awal) - Eko Supendi (Gelar : Jurnal Seni Budaya, 2007)
Wayang wong, as a genre included in dance drama, is in fact the  personification of wayang kulit purwo of which the stories come from the Ramayana  and Mahabarata. The existence of wayang wong in Mangkuneagaran Palace and  in the Sultanate of Jogjakarta in second half of the 18th century was the renaissance  of wayang wong which had developed in the time of the empire of Majapahit.  Even it was supposed to have developed before that time because in the year of 930  the term of wayang wong was discovered in the inscription of Wimalasrama.Semiotics can be defined in a simple way as knowledge of signs and system  of signs. Some People say that semiotics is knowledge dealing sistematically with  signs,  symbols and process of symbolism. This simple definition will turn into complex ·  one when there is a demand to define a sign. The difficulty in coming to an agreement  on the definition of signs can make the agreement on the definition of semiotics  difficult.Keywords: Wayang orang, Traditional Theatre, Semiotics